Methodological approaches of Shaykh Aminul Islam in dealing with the Qur'an : an analytical study of his tafsir "Tafsir-E-Nurul Qur'an" - Mohammad Abdul Zalil (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Shaykh Aminul Islam’s magnum opus writing, “Tafsir-e-Nurul Qur’an” is regarded as one of the most comprehensive Qur’anic interpretation for Bengali speaking people. It is one of the most widely read tafsir in Bangladesh as Shaykh Aminul Islam directed his attention towards the message of the Qur’an based on the contemporary issues and the different perceptions of the people. The unique characteristics of this tafsir is based on Tafsir al-Mawdu`i or thematic interpretation of the Qur’an. The main purpose of this study is to expose the personality of Shaykh Aminul Islam to the readers, to present his monumental tafsir of the Qur’an and evaluate its fundamental features. The research adopted textual, descriptive and critical analysis to present the scenario of the tafsir literatures in Bangladesh, evaluate the stand of Shaykh Aminul Islam in the existing literatures. The study objectively evaluates the position of Tafsir-e-Nurul Qur’an in the context of both traditional and modern tafsir. This research appreciates, acknowledges and sometimes critically examines the viewpoints of Shaykh Aminul Islam in his tafsir. The research revolves around Shaykh Aminul Islam’s tafsir, his writings on various issues, traditional and modern tafsir and the fundamental sources of Islam. The study reached some conclusions that deserve attention. Shaykh Aminul Islam’s writings played important role in shaping the character and values of youths in Bangladesh. He followed a thematic approach in explaining the Qur’an. His interpretation remained objective without being biased for any sect or group. He followed a traditional cum rational approach in his interpretation. His inclination towards sufi’s trend is also noticeable so much that sometimes he accepts their views without sound judgment. However, Shaykh Aminul Islam’s overall contributions to the tafsir and literature in Bengali are truly remarkable.